Effectiveness of Prophetic Education in Reducing Stereotypical Behavior and Suspicion among Early Childhood Learners - Mubiar Agustin; Asep Deni Gustiana; Idat Muqodas; Aam Imaddudin; Yoga Adi Pratama (Celebes Journal of Elementary Education, 2026)
This study investigates the effectiveness of the Prophetic Education Program in reducing stereotypical behavior and suspicion in early childhood while exploring its impact on strengthening sustainable education in Indonesia. Grounded in the concept of Prophetic Education, which integrates the values of the Prophet Muhammad through four approaches: structural, formal, mechanical, and organic, this study aligns with Sustainable Development Goal 4, which promotes inclusive and quality education. Using a quasi-experimental design, the study involved 340 early childhood students divided into experimental and control groups, with the experimental group participating in the Prophetic Education Program. Data were collected using questionnaires administered with teacher assistance and analyzed using an independent samples t-test to measure behavioral differences between groups. The test confirmed a statistically significant difference between groups (t = [nilai t], p < 0.001, M experimental = 1.84, M control = 2.39). In the experimental group, 91.18% of children never exhibited stereotypical behavior and 92.94% never showed suspicion, compared to 77.06% and 82.35% in the control group. These findings highlight the role of value-based education in promoting inclusivity and moral development. The study offers practical implications for early childhood education, demonstrating how Prophetic Education can be integrated into the curriculum to create inclusive, sustainable learning environments. Moreover, it provides valuable insights for educators and policymakers on the importance of Islamic value-based interventions in achieving SDGs. The study's originality lies in its innovative integration of prophetic values with sustainable development principles.